Research for Ethiopia's Agriculture Policy (REAP) - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
The Research for Ethiopia’s Agriculture Policy (REAP) project is designed to support the Ethiopian Agricultural Transformation Agency (ATA). Researchers will identify shortfalls in Ethiopia's agricultural sector and recommend solutions to the ATA.